2014
DOI: 10.3390/rs6043427
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Fractional Shrub Cover Using Simulated EnMAP Data: A Comparison of Three Machine Learning Regression Techniques

Abstract: Anthropogenic interventions in natural and semi-natural ecosystems often lead to substantial changes in their functioning and may ultimately threaten ecosystem service provision. It is, therefore, necessary to monitor these changes in order to understand their impacts and to support management decisions that help ensuring sustainability. Remote sensing has proven to be a valuable tool for these purposes, and especially hyperspectral sensors are expected to provide valuable data for quantitative characterizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
60
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 66 publications
(62 citation statements)
references
References 45 publications
1
60
1
Order By: Relevance
“…Several studies plotted unmixed fraction versus RD fraction and computed a linear regression of the result. Using this technique, perfect unmixing would result in an R 2 and slope equal to unity, with the intercept equal to zero [10,13].…”
Section: Comparison Of Unmixing Results and Amrdmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies plotted unmixed fraction versus RD fraction and computed a linear regression of the result. Using this technique, perfect unmixing would result in an R 2 and slope equal to unity, with the intercept equal to zero [10,13].…”
Section: Comparison Of Unmixing Results and Amrdmentioning
confidence: 99%
“…These studies also implemented methods to compare AMRD with spectral unmixing results, with the most common strategy being calculation of mean absolute error (MAE) and/or root-mean square error (RMSE) [11][12][13]. Several studies plotted unmixed fraction versus RD fraction and computed a linear regression of the result.…”
Section: Comparison Of Unmixing Results and Amrdmentioning
confidence: 99%
See 1 more Smart Citation
“…In this paper, we present some of the preparatory research activities of the EnMAP Scientific Advisory Group (EnSAG) on natural ecosystems and ecosystem transitions (EnSAG-Ecosystems), alongside the work previously published [37,43] and that published in the current issue [53]. Our aim is to demonstrate the benefit from high quality spaceborne IS data, like EnMAP, for characterizing and quantifying gradual ecosystem transitions and natural ecosystems.…”
Section: Introductionmentioning
confidence: 99%
“…Few studies have so far used simulated EnMAP data [42] to monitor gradual ecosystem changes [28,37,43]. The high temporal and systematic coverage of the EnMAP system will allow for continuous monitoring and the study of ecosystem processes and properties [44], as demonstrated by some pilot studies using data from experimental spaceborne systems [45,46].…”
Section: Introductionmentioning
confidence: 99%